Expression of vitamin D receptor and vitamin D status in patients with oral neoplasms and effect of vitamin D supplementation on quality of life in advanced cancer treatment - Anand, Akshay; Singh, Suyash; Sonkar, Abhinav A.; Husain, Nuzhat; Singh, Kul Ranjan; Singh, Sudhir; Kushwaha, Jitendra K. (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study: Vitamin D receptor (VDR) expression and serum vitamin D scores in oral premalignant lesions and oral cancer have not been widely analyzed. The role of vitamin D supplementation in advanced oral cancer for improving quality of life (QOL) is also a matter of research. Material and methods: Vitamin D receptor expression and vitamin D scores were analyzed in normal oral mucosa (n = 95), leukoplakia (n = 23) and oral cancer (n = 87). 45 patients with advanced oral cancer subjected to chemoradiation were evaluated for the effect of vitamin D supplementation on most observable QOL parameters such as oral mucositis, swallowing performance and overall QOL. Results: Vitamin D receptor expression was increased in oral neoplastic lesions. Vitamin D scores were significantly lower in cases compared to healthy controls (p = 0.002). Vitamin D supplementation significantly reduced the therapy-related toxicities in advanced cancer, thus reducing morbidity and improving QOL. Conclusions : Vitamin D receptor expression is increased in premalignant lesions and oral cancer. Vitamin D insufficiency and deficiency are prevalent in patients with oral neoplastic lesions. Vitamin D supplementation has a role in reducing treatment-related toxicities, especially in advanced cancer.